2015
DOI: 10.5114/reum.2015.53135
|View full text |Cite
|
Sign up to set email alerts
|

Pain associated with the musculoskeletal system in children from Warsaw schools

Abstract: ObjectiveTo assess the prevalence of pain in the musculoskeletal system and possible reasons for these complaints among early age children from Warsaw schools.Material and methodsThe study was conducted in 34 randomly selected primary schools in Warsaw in 2011. 2748 survey-questionnaires were given to parents or legal guardians by children. Of these, 1509 surveys were subject to a final analysis. The survey included 66 questions regarding, among other things, pain in the musculoskeletal system in children. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Another issue in relation to heterogeneity is that there are challenges with use of questionnaires within this age group. In seven of the 19 general population studies, questionnaires or text messages were answered by parents [ 14 , 39 , 40 , 47 , 49 , 51 , 53 ]. Therefore, the concordance between parents’ and children’s reporting is important to understand.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue in relation to heterogeneity is that there are challenges with use of questionnaires within this age group. In seven of the 19 general population studies, questionnaires or text messages were answered by parents [ 14 , 39 , 40 , 47 , 49 , 51 , 53 ]. Therefore, the concordance between parents’ and children’s reporting is important to understand.…”
Section: Discussionmentioning
confidence: 99%
“…In this analysis, the prevalence of back pain was 10.0–76.2% in 17 studies 3,21–23,25,29,30,114,119,126,128–134 (Table 4), neck pain was 5.0–49.0% in 15 studies, 28,29,113,114,119,122,125,127,135–141 shoulder pain was 9.6–48.0% in eight studies, 28,29,113,114,122,138,141,142 and spinal pain was 14.2–66.0% in six studies 116,118,139,143–145 . In studies where a breakdown of pain in different regions of the back was available, the prevalence of pain ranged from 4.0–57.0% for the lower back in 23 studies, 28,114,115,117,119–125,127,130,135–138,141,146–150 3.4–41.3% for the upper back in nine studies, 28,114,122,123,127,130,137,138,141 and 4–35% for the middle back in four studies 125,130,135,151 .…”
Section: Resultsmentioning
confidence: 85%
“…Both CPSP and persistent pain can have a deleterious impact on the expected functional outcomes of the surgery. Research in adults without disabilities has demonstrated that CPSP commonly interferes with activities of daily living, sleep, and quality of life 26 and impacts long‐term functional outcomes such as mobility and range of motion 27,28 . Not surprisingly, little is known about the prevalence and characteristics of persistent pain after surgery or how pain impacts functional outcomes in children with CP.…”
Section: Introductionmentioning
confidence: 99%
“…Research in adults without disabilities has demonstrated that CPSP commonly interferes with activities of daily living, sleep, and quality of life 26 and impacts long‐term functional outcomes such as mobility and range of motion. 27 , 28 Not surprisingly, little is known about the prevalence and characteristics of persistent pain after surgery or how pain impacts functional outcomes in children with CP. However, limited case series have demonstrated that pain following SEMLS procedures in patients with CP have negatively impacted their ability to comply with physiotherapy and their ability to bear weight.…”
Section: Introductionmentioning
confidence: 99%